CALCULATION MODEL OF THE SYSTEM OF THERMAL STABILIZATION OF THE ELEMENTS OF RADIO ELECTRONIC EQUIPMENT - T. A. Ismailov; A. M. Ibragimova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the study is to develop a computational model of the system of thermal stabilization of elements of electronic equipment (REA), based on the joint use of working substances with a stable melting point and the liquid method of heat sink, the study of the thermophysical processes occurring during its operation.Method. A computational model of the REA thermostabilization system based on the use of working substances with a stable melting point has been created. The model includes a description of the heat exchange processes during laminar fluid motion in a heat exchanger, determining the duration of stable operation of the REA elements, depending on the flow rate and cooling capacity of a thermoelectric battery (TEB).Result. The graphs of dependences reflecting the main characteristics of the developed system were obtained, in particular, the dependence of the change in the duration of maintaining the stable temperature of the REA element on its power, the temperature of the cold junctions of the thermopile, scattering at different maximum flow rates of the heat exchanger.Conclusions. The results of the calculations determine that the duration of complete penetration of the working substance, corresponding to the duration of stable operation of CEA elements, can be within the required limits only if certain very specific conditions are met: using a sufficient amount of the working substance in the heat stabilizing system, corresponding to the temperature and flow rate of the liquid in the heat exchanger. These parameters of the thermal stabilization system must be selected based on the amount of heat emitted per unit of time by the REA element, the duration of its operation, and the characteristics of the thermopile used to cool the fluid.